2022
DOI: 10.3389/fendo.2022.816970
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Reference Intervals for Thyroid-Associated Hormones Using refineR Algorithm in Chinese Population at High-Altitude Areas

Abstract: ObjectivesDiagnosis of thyroid disease among individuals dwelling at high altitude remains a challenge. Reference intervals (RIs) for thyroid-associated hormones among Tibetans living at various high altitudes were established to improve diagnosis.MethodsOne thousand two hundred eighty-one subjects were randomly recruited from Nyingchi, Shigatse/Lhasa, and Ali of Tibet. Thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) were measured by the Cobas e601 electrochemiluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Considering China’s unique ladder-like terrain, we aimed to describe the hyperthyroidism prevalence based on topographic factors. Several studies explored the thyroid status and thyroid disorder prevalence in Tibet (first ladder region) with a small sample size [ 15 , 20 , 36 ]. Furthermore, they only investigated Tibetan regions without comparisons with the other two ladder regions of China with a limited population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering China’s unique ladder-like terrain, we aimed to describe the hyperthyroidism prevalence based on topographic factors. Several studies explored the thyroid status and thyroid disorder prevalence in Tibet (first ladder region) with a small sample size [ 15 , 20 , 36 ]. Furthermore, they only investigated Tibetan regions without comparisons with the other two ladder regions of China with a limited population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, diagnosis of thyroid disease among individuals dwelling at high altitudes remains a challenge. Recently, a study investigated thyroid-associated hormones of 1281 participants living in Tibet, the first ladder region of China, and established altitude-specific RI for thyroid-related hormones among residents living in high altitude [ 15 ]. They found that FT3 increased with altitude, while FT4 was less influenced by altitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering China's unique ladder-like terrain, we aimed to describe the hyperthyroidism prevalence based on topographic factors. Several studies explored the thyroid status and thyroid disorder prevalence in Tibet ( rst ladder) with a small sample size (13,30,31). Furthermore, they only investigated Tibetan regions without comparisons with the other two ladder regions of China with a limited population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few small, population-based studies explored the association between thyroid status and the rst ladder region of Tibet, although these studies did not compare thyroid status with the other two Chinese ladder regions (13). Furthermore, an Ethiopian study reported that altitude correlated with goiter prevalence, with the peak prevalence observed in the highlands (14).…”
Section: Introductionmentioning
confidence: 99%